Precipitated silica and its manufacturing process

JP7602568B2Active Publication Date: 2024-12-18RHODIA OPERATIONS SAS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023058073
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-04-12
Filing Date
2023-03-31
Publication Date
2024-12-18
Estimated Expiration
2038-12-20

Smart Images

  • Figure 0007602568000001
    Figure 0007602568000001
  • Figure 0007602568000002
    Figure 0007602568000002
  • Figure 0007602568000003
    Figure 0007602568000003
Patent Text Reader

Abstract

To provide a novel chemically modified precipitated silica that can be used as a reinforcing filler in polymer compositions.SOLUTION: Provided is a precipitated silica comprising alkyl moieties chemically bound to at least a part of Si atoms in a silica structure characterized in that the resonance assigned to methyl groups in the alkyl moieties in the 13CNMR spectrum of the precipitated silica is between -2.5 and -4.5 ppm. A process for preparing the precipitated silica comprises the reaction of a silicate with an acid to produce a suspension of precipitated silica, the reaction comprising at least one step wherein at least one alkali metal alkyl siliconate is provided to the reaction medium before 50% of the precipitation reaction has taken place.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to European Patent Application Publication No. 17306937.8, filed December 27, 2017, and European Patent Application Publication No. 18305450.1, filed April 12, 2018, the entire contents of which are incorporated herein by reference for all purposes.

[0002] The present invention relates to chemically modified precipitated silica and a process for its manufacture. [Background technology]

[0003] The use of precipitated silica as a reinforcing filler in polymer compositions is known. A problem associated with the use of precipitated silica in polymer compositions, especially elastomeric compositions, is that the degree of dispersion in the polymer matrix is ​​rather low. The chemical modification of the surface of precipitated silica with organosilicon compounds is known to improve the compatibility of the precipitated silica with the polymer matrix. The organosilicon compounds are typically selected from trialkylsilanes, dialkylsilanes, trialkylalkoxysilanes, trialkylhalosilanes, dialkylalkoxysilanes, dialkyldialkoxysilanes, dialkylalkoxyhalosilanes, trialkylsilanols, alkyltrialkoxysilanes, alkyldialkoxysilanes, alkyldialkoxyhalosilanes, and monoalkylsilanes, where the alkyl group is a linear, cyclic or branched hydrocarbon having 1 to 18 carbon atoms, optionally containing a sulfur atom and / or a functional group. Generally, the chemical modification is carried out on the precipitated silica at the end of the silica precipitation process, often as an additional step after drying.

[0004] It has now been found that by using alkali metal alkyl siliconates, modification during the silica precipitation reaction can be used to obtain chemically modified precipitated silicas with good reinforcement and good mechanical properties. The presence of the alkali metal alkyl siliconates in the reaction medium since the initial stage of the silica formation process allows the formation of chemically modified silicas with alkyl groups. The chemical modification of the silica is carried out during the precipitation process without the need for a subsequent modification step.

[0005] The use of alkali metal alkyl siliconates for surface modification of silica aerogels has been disclosed. For example, US Pat. No. 2,945,817 discloses a process for preparing an aerogel, which comprises preparing a solution containing sodium silicate and an alkali metal alkyl siliconate, adding an acid to obtain an aqueous sol, and removing water from the aqueous sol by distilling the water in an azeotropic mixture with a suitable alcohol. Also, British Patent No. 607,427 and WO 16,050,474 A1 disclose water-repellent aerogels prepared using alkali metal alkyl siliconates. However, none of these documents discloses the chemical modification of precipitated silica with alkali metal alkyl siliconates. Summary of the Invention

[0006] A first object of the present invention is to provide novel chemically modified precipitated silicas which can be used, for example, as reinforcing fillers in polymer compositions. A second object of the present invention is to provide a process for the manufacture of chemically modified precipitated silicas which has the advantage that the modification is carried out during the silica precipitation process.

[0007] The precipitated silicas of the invention are characterized, inter alia, by the presence of alkyl groups covalently bonded to the silica.The silicas of the invention are defined in detail in the following description and in the claims and examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The precipitated silica of the present invention contains chemically bonded alkyl moieties, and the methyl groups of said alkyl moieties are assigned to the precipitated silica. 13 It is characterized by a C NMR spectrum with a resonance of -2.5 to -4.5 ppm.

[0009] The silica of the present invention contains alkyl moieties chemically bonded to at least some of the Si atoms in the silica structure. 13 The resonances of the C NMR spectrum are between -2.5 and -4.5 ppm.

[0010] As used herein, the expression "alkyl moiety" refers to a group represented by the general formula (C m H 2m+1 The structure of the silica of the present invention is of the formula [SiO 4 / 2 ] and the formula [(C m H 2m+1 )SiO 3 / 2 ] and the unit is described as including.

[0011] In this specification, the terms "silica" and "precipitated silica" are used synonymously. The expression "precipitated silica" defines an amorphous silica produced by acidification of a solution of sodium silicate, followed by filtration of the precipitate and drying without any step of extracting water from the precipitate using an organic solvent, for example an alcohol or a supercritical fluid.

[0012] The alkyl moieties are derived from at least one alkali metal alkyl siliconate. Suitable alkali metal alkyl siliconates have the general formula (I): HO-[Si(R)(OM)-O-] n H(I) (wherein n is an integer of 1 to 6, particularly 1 to 3, preferably n is 1; R is a group represented by the formula (C m H 2m+1)-, where m is an integer from 1 to 5, in particular from 1 to 3, particularly preferably methyl is 1 and M is an alkali metal, preferably sodium or potassium.

[0013] The chemically bonded alkyl moieties in the silica of the present invention are preferably selected from the group consisting of methyl, ethyl and propyl, and are linear or branched. In a preferred embodiment, the chemically bonded alkyl moieties are methyl. In such an embodiment, the alkali metal alkyl siliconate is selected from sodium or potassium methyl siliconate.

[0014] The precipitated silica of the present invention 13 The C NMR spectrum is characterized by the resonances of chemically bound methyl groups between -2.5 and -4.5 ppm. The expression "resonances between -2.5 and -4.5 ppm" means that when the chemical shift scale is calibrated to the resonances of adamantane (38.5 ppm and 29.4 ppm), the maximum of the resonance peaks assigned to the methyl groups is between -2.5 and -4.5 ppm. 13 It is used herein to indicate presence in the region of the C NMR spectrum.

[0015] The resonances assigned to the methyl groups of the chemically bonded alkyl moieties in the silica of the present invention are observed to be shifted relative to the resonances of the same methyl groups in the alkali metal alkyl siliconate used to prepare the precipitated silica, for example, when the alkali metal alkyl siliconate is potassium methyl siliconate, the methyl resonances are shifted from -1.1 ppm to the range of -2.5 to -4.5 ppm.

[0016] The precipitated silica of the present invention has a carbon content of at least 0.2% by weight, typically between 0.2% and 15.0% by weight. Throughout the text, the carbon content is defined as the weight of carbon relative to the weight of silica. The carbon content represents the amount of alkyl moieties chemically bonded to the precipitated silica. The carbon content is typically less than 10.0% by weight, and may even be less than 5.0% by weight. Advantageously, the carbon content is between 0.2% and 5.0% by weight, or even between 0.3 and 2.0% by weight. The carbon content may be between 0.2% and 1.0% by weight, or even between 0.3 and 1.0% by weight.

[0017] The expressions wt% and % by weight are used synonymously.

[0018] Generally, the precipitated silica according to the invention has a melting point of 40 to 600 m 2 / g. The CTAB surface area is at least 50 m 2 / g, at least 60m 2 / g, at least 80m 2 / g, and at least 120m 2 / g, at least 160m 2 / g, at least 205m 2 / g, at least 210m 2 / g. The BET specific surface area is at most 450 m 2 / g, at most 380m 2 / g, and even at most 300m 2 The CTAB surface area can be in particular between 50 and 450 m 2 / g, especially 60-380m 2 / g, e.g. 80~300m 2 / g.

[0019] In a first embodiment, the precipitated silica of the invention has -40m 2 / g~600m 2 / g, preferably 40m 2 / g~380m 2 / g, more preferably 40m 2 / g~300m 2 / g CTAB surface area, and It is characterized by a carbon content between 0.2% and 1.0% by weight, preferably between 0.3% and 1.0% by weight.

[0020] In a second embodiment, the precipitated silica of the invention has -205m 2 / g~600m2 / g, preferably 210m 2 / g~450m 2 / g CTAB surface area, and It is characterized by a carbon content between 0.2% and 5.0% by weight, preferably between 0.3% and 5.0% by weight.

[0021] The precipitated silica according to the present invention is typically 45 ml 2 / g~650m 2 / g, especially 70m 2 2 / g~500m 2 / g, and even 90-400m 2 / g, e.g., 90-370m 2 / g. The BET surface area can be determined according to the Brunauer-Emmett-Teller method detailed in standard NF ISO 5794-1, Appendix E (June 2010).

[0022] The precipitated silica according to the invention has a viscosity of at most 0.50 g / cm, measured according to standard ISO 787 / 11. 3 , preferably 0.15 to 0.50 g / cm 3 , especially 0.15 to 0.40 g / cm 3 has a packing density of

[0023] The precipitated silica of the invention can be advantageously obtained by a process comprising reacting a silicate with an acid to produce a suspension of precipitated silica, said reaction comprising at least one step in which at least one alkali metal alkyl siliconate is provided to the reaction medium before 50% of the precipitation reaction has taken place.

[0024] A second object of the present invention is therefore the process for the preparation of the precipitated silica of the present invention.

[0025] The process involves reacting a silicate with an acid to produce a suspension of precipitated silica, said reaction including at least one step in which at least one alkali metal alkyl siliconate is provided to the reaction medium before 50% of the precipitation reaction has taken place.

[0026] The term "silicate" is used herein to refer to one or more silicates that may be added during the process of the present invention. The term "silicate" is used herein to refer to a compound selected from the group consisting of alkali metal silicates. Advantageously, the silicate is selected from the group consisting of sodium silicate and potassium silicate. The silicate may be in any known form, such as metasilicate or disilicate.

[0027] If sodium silicate is used, the latter generally has a SiO2 / Na2O weight ratio of 2.0 to 4.0, in particular 2.4 to 3.9, for example 3.1 to 3.8.

[0028] Generally, the silicate is provided as a solution having a concentration typically between 3.9% and 25.0% by weight, for example between 5.6% and 23.0% by weight, in particular between 5.6% and 20.7% by weight. Throughout the text, the silicate concentration in the solution is expressed as the weight of SiO2.

[0029] The term "acid" is used herein to refer to one or more acids that may be added during the process of the present invention. Any acid may be used in the process. Typically, mineral acids such as sulfuric acid, nitric acid, or hydrochloric acid, or organic acids such as acetic acid, formic acid, or carbonic acid are used. Sulfuric acid is preferred.

[0030] The acid may be metered into the reaction medium in dilute or concentrated form. Different concentrations of the same acid may be used at different stages of the process.

[0031] In a preferred embodiment of the process, sulfuric acid and sodium silicate are used at all stages of the process.

[0032] The process of the invention is characterized in that at least one alkali metal alkyl siliconate is added to the reaction medium before 50% of the precipitation reaction has taken place.

[0033] Before 50% of the precipitation reaction has taken place, a total amount of at least one alkali metal alkyl siliconate can be added to the reaction medium.

[0034] The expression "before 50% of the precipitation reaction has taken place" is used herein to refer to any stage of the process where the amount of SiO2 produced by said given stage is less than 50% by weight of the final amount of SiO2 produced in the process.

[0035] Depending on the process, the rate of silica precipitation can be monitored in various ways. In one process variant, the formation of 50% by weight of the total amount of silica corresponds to the addition to the reaction medium of 50% of the total amount of silicate added during the process.

[0036] In another variation, the formation of 50% by weight of the total amount of silica is achieved when the neutralization rate of the reaction medium reaches 50%. The term "neutralization ratio" refers to the ratio of the H produced by the acid added to the reaction medium. + to the number of moles of alkali metal derived from silicate in the reaction medium.

[0037] Without wishing to be bound by theory, it is believed that adding at least one alkali metal alkyl siliconate before 50% of the precipitation reaction has taken place allows the alkyl moieties of the alkali metal alkyl siliconate to be incorporated into the structure of the precipitated silica.

[0038] Notable examples of suitable alkali metal alkyl siliconates include those represented by the general formula (I) above: HO-[Si(R)(OM)-O-] n H(I) (wherein n is an integer of 1 to 6, particularly 1 to 3, preferably 1; R is a group represented by the formula (C m H 2m+1 )-, where m is an integer from 1 to 5, in particular from 1 to 3, particularly preferably m is 1 and M is an alkali metal, preferably sodium or potassium.

[0039] In formula (I), preferably, n=1 and R is selected from the group consisting of methyl, ethyl and propyl, and is linear or branched. In a preferred embodiment, n=1 and R is methyl. In such an embodiment, the alkali metal alkyl siliconate is selected from sodium or potassium methyl siliconate.

[0040] The definitions and preferences provided above also apply to specific embodiments of the processes described herein below.

[0041] In a first embodiment, the process comprises: (i) providing a starting solution comprising at least a portion of the total amount of alkali metal alkyl siliconates, at least a portion of the total amount of silicates participating in the reaction, and optionally an electrolyte, wherein the concentration of silicates present in the starting solution (expressed as SiO2) is less than 100 g / L; (ii) adding an amount of acid to said starting solution to obtain a pH value of the reaction medium of at least 7.0, in particular between 7.0 and 8.5; (iii) further adding acid and, if appropriate, simultaneously the remaining amount of silicate to the reaction medium to obtain a silica suspension.

[0042] In this first embodiment of the process, at least a portion of the total amount of at least one alkali metal alkyl siliconate is present in the starting solution, and the remaining portion of the at least one alkali metal alkyl siliconate may be added to the reaction medium during the silica precipitation reaction, in particular during step (ii) or (iii), with the proviso that all of the alkali metal alkyl siliconate is added before 50% of the precipitation reaction has taken place.

[0043] Alternatively, a total amount of at least one alkali metal alkyl siliconate can be provided in the starting solution.

[0044] In a first embodiment of the process, the point at which 50% of the precipitation reaction is carried out corresponds to the neutralization ratio defined above.

[0045] The starting solution of step (i) may contain one or more electrolytes. Preferably, the starting solution contains an electrolyte, advantageously the concentration of said electrolyte is less than 19 g / L. The term "electrolyte" is used herein in its generally accepted sense, i.e. to identify any ionic or molecular substance that, when in solution, decomposes or dissociates to form ions or charged particles. Mention may be made of salts selected from the group consisting of salts of alkali metals and alkaline earth metals. Advantageously, the electrolyte used in the starting solution is a salt of the metal and acid of the starting silicate used in the process. Notable examples are sodium chloride in the case of the reaction of sodium silicate with hydrochloric acid, or, preferably, sodium sulfate in the case of the reaction of sodium silicate with sulfuric acid.

[0046] In a second embodiment, the process comprises the steps of: (i) providing a starting solution having a pH of 2.0 to 5.0, preferably 2.5 to 5.0; (ii) adding silicate and acid simultaneously to the starting solution and maintaining the pH of the resulting reaction medium between 2.0 and 5.0; (iii) stopping the addition of acid while continuing the addition of silicate to the reaction medium until a pH value of the reaction medium between 7.0 and 10.0 is obtained; (iv) adding silicate and acid simultaneously to the reaction medium obtained in (iii) and maintaining the pH at 7.0 to 10.0; (v) stopping the addition of silicate while continuing the addition of acid to the reaction medium until the pH value of the reaction medium reaches less than 6.0 and a silica suspension is obtained.

[0047] In this second embodiment of the process, at least one alkali metal alkyl siliconate is metered into the reaction medium in at least one of steps (i) or (ii), with the proviso that said addition is carried out before adding 50% of the total amount of silicate to the reaction medium. The total amount of silicate to obtain a given final amount of silica can be determined by the person skilled in the art at the beginning of the process according to common general knowledge.

[0048] The process of this second embodiment may include further steps, in particular steps in which the pH is further varied by the addition of silicates and / or acids to the reaction medium.

[0049] In a third embodiment, the process comprises the steps of: (i) providing a starting solution containing a portion of the total amount of silicate participating in the reaction, said starting solution having a silicate concentration (expressed as SiO2) of less than 20 g / L, preferably less than or equal to 15 g / L; (ii) adding an acid to said starting solution until at least 50% of the amount of silicate present in said starting solution is neutralized; (iii) adding silicate and acid simultaneously to the reaction medium, the ratio (amount of silicate added) / (amount of silicate present in the starting solution) being greater than 4 and less than or equal to 100, preferably between 12 and 100, in particular between 12 and 50; (iv) stopping the addition of silicate while continuing the addition of acid to the reaction medium until the pH of the reaction medium reaches a value between 2.5 and 5.3, preferably between 2.8 and 5.2, and a suspension of precipitated silica is obtained.

[0050] In this embodiment, at least one alkali metal alkyl siliconate is metered into the reaction medium in at least one of steps (i), (ii), and (iii), provided that said addition occurs before 50% of the total amount of silicate has been added to the reaction medium.

[0051] In all process embodiments outlined above, regardless of the stage of addition of at least one alkali metal alkyl siliconate, the cumulative amount of the aforementioned compounds metered into the reaction medium is at least 0.5% by weight, typically at least 1.0% by weight, or even at least 5.0% by weight. The total amount of at least one alkali metal alkyl siliconate typically does not exceed 30.0% by weight, preferably does not exceed 25.0% by weight. Suitable ranges are generally 1.0-20.0% by weight, 5.0-15.0% by weight, or even 5.0-12.0% by weight. The amount of methyl siliconate is calculated relative to the silicic acid concentration of the starting solution (calculated as the sum of the initial amount of silicate and the initial amount of alkali metal alkyl siliconate).

[0052] The cumulative amount of the aforementioned compounds metered into the reaction medium is such that the carbon content of the precipitated silica is at least 0.2% by weight, typically 0.2-15.0% by weight. The rate of addition of the alkali metal alkyl siliconate can be adapted by means known to those skilled in the art to obtain the desired content of alkyl moieties in the precipitated silica.

[0053] The reaction vessel in which the entire reaction between the silicate and the acid is carried out is usually equipped with suitable stirring and heating devices.

[0054] The overall reaction of the silicate with the acid is generally carried out at a temperature between 40 and 96° C., in particular between 80 and 95° C. According to one variant of the invention, the overall reaction of the silicate with the acid is generally carried out at a constant temperature between 40 and 96° C., in particular between 80 and 95° C.

[0055] According to another variant of the invention, the temperature at the end of the reaction is higher than the temperature at the beginning of the reaction, which is therefore preferably maintained at 40-80° C., and then the temperature is preferably increased to a value between 80 and 96° C. and maintained at that value until the end of the reaction.

[0056] At the end of the steps just described for each of the process embodiments, a suspension of precipitated silica is obtained, which is then subjected to a separation step (liquid / solid separation).The process in all of its embodiments therefore typically includes the further steps of filtering the suspension of precipitated silica and drying the precipitated silica.This process does not include a step of extracting water from the precipitate using an organic solvent, such as an alcohol, or a supercritical fluid.

[0057] This separation usually involves filtration, followed by washing if necessary, which is carried out according to any suitable method, for example by means of a belt filter, a rotary filter (e.g. a vacuum filter) or, preferably, a filter press.

[0058] The filter cake is then subjected to a liquefaction operation. The term "liquefaction" is intended herein to denote the process by which a solid, i.e., the filter cake, is converted into a fluid-like mass. After the liquefaction step, the filter cake is in a flowable, fluid-like form and the precipitated silica is in suspension.

[0059] The liquefaction step may include a mechanical treatment that results in a reduction in the particle size distribution of the suspended silica. Said mechanical treatment may be carried out by passing the filter cake through a high shear mixer, a colloid type mill or a ball mill. Optionally, the liquefaction step may be carried out by subjecting the filter cake to chemical action, for example by adding water or an acid. Both mechanical and chemical treatments may be carried out. The suspension of precipitated silica obtained after the liquefaction step is then dried.

[0060] Drying can be carried out according to techniques known in the art. Preferably, drying is carried out by spraying. For this purpose, any type of suitable sprayer can be used, in particular turbine, nozzle, liquid pressure or two-fluid sprayers. Generally, when filtration is carried out using a filter press, a nozzle type sprayer is used, and when filtration is carried out using a vacuum filter, a turbine type sprayer is used.

[0061] If the drying operation is carried out using a nozzle type atomizer, the precipitated silica obtained is usually in the form of substantially spherical beads. After this drying operation, the recovered product can optionally be subjected to a grinding or pulverization step, and the precipitated silica obtained is generally in the form of a powder.

[0062] If the drying operation is carried out by means of a turbine atomizer, the precipitated silica obtainable may be in the form of a powder.

[0063] Finally, the product, dried, ground or pulverized as indicated above, is optionally subjected to an agglomeration step, which consists, for example, of direct compression, wet granulation (i.e. by using a binder such as water, silica suspension, etc.), extrusion or preferably dry compaction.

[0064] The precipitated silica obtainable by this agglomeration process is generally in the form of granules.

[0065] The precipitated silica of the present invention can be used in many applications, such as in the manufacture of thermal insulation materials, and in the preparation of resorcinol-formaldehyde / silica composites, as an absorbent or as an additive in concrete or paper.

[0066] The precipitated silicas of the present invention may find particularly advantageous use as fillers in polymer compositions.

[0067] A further object of the present invention is therefore a composition comprising the precipitated silica of the present invention. The composition advantageously comprises the precipitated silica of the present invention and at least one polymer. The at least one polymer can be chosen from thermosetting polymers and thermoplastic polymers. Notable non-limiting examples of thermosetting polymers include thermosetting resins such as epoxy resins, unsaturated polyester resins, vinyl ester resins, phenolic resins, epoxy acrylate resins, urethane acrylate resins, phenoxy resins, alkyd resins, urethane resins, maleimide resins and cyanate resins.

[0068] Notable non-limiting examples of suitable thermoplastic polymers include polystyrene, (meth)acrylic acid ester / styrene copolymers, acrylonitrile / styrene copolymers, styrene / maleic anhydride copolymers, styrenic polymers such as ABS, ASA, and AES, acrylic polymers such as polymethyl methacrylate, polycarbonates, polyamides, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyphenylene ethers, polysulfones, polyaryletherketones, polyphenylene sulfides, thermoplastic polyurethanes, polyolefins such as polyethylene, polypropylene, polybutene, poly-4-methylpentene, ethylene / propylene copolymers, ethylene / α-olefin copolymers, copolymers of α-olefins with various monomers such as ethylene / vinyl acetate copolymers, ethylene / (meth)acrylic acid ester copolymers, ethylene / maleic anhydride copolymers, ethylene / acrylic acid copolymers, aliphatic polyesters such as polylactic acid, polycaprolactone, and aliphatic glycol / aliphatic dicarboxylic acid copolymers.

[0069] The silica of the invention can be advantageously used as a reinforcing filler in elastomer compositions. A preferred object of the invention is therefore a composition comprising the silica of the invention and one or more elastomers. The elastomers preferably exhibit at least one glass transition temperature between -150°C and +300°C, for example between -150°C and +20°C.

[0070] For example, elastomers derived from aliphatic or aromatic monomers containing at least one unsaturation, such as ethylene, propylene, butadiene, isoprene, styrene, acrylonitrile, isobutylene or vinyl acetate, polybutyl acrylate or mixtures thereof, among others, may be used. Mention may also be made of functionalized elastomers, which are elastomers functionalized by chemical groups located along the polymer chain and / or at one or more of its ends (for example by functional groups capable of reacting with the surface of the silica) and halogenated polymers.

[0071] Notable but non-limiting examples of suitable elastomers are diene elastomers. Among diene elastomers, mention may be made, for example, of polybutadiene (BR), polyisoprene (IR), butadiene copolymer, isoprene copolymer, or mixtures thereof, in particular styrene / butadiene copolymer (SBR, in particular ESBR (emulsion) or SSBR (solution)), isoprene / butadiene copolymer (BIR), isoprene / styrene copolymer (SIR), isoprene / butadiene / styrene copolymer (SBIR), ethylene / propylene / diene terpolymer (EPDM), and also related functionalized polymers (presenting pendant polar groups or polar groups at chain ends that can interact with silica, for example).

[0072] Mention may also be made of natural rubber (NR) and epoxidized natural rubber (ENR).

[0073] The polymeric composition may be sulfur vulcanized or crosslinked, among others, with peroxides or other crosslinking systems (eg, diamines or phenolic resins).

[0074] Generally, the polymer composition further comprises at least one (silica / polymer) coupling agent and / or at least one coating agent, which may further comprise, inter alia, an antioxidant.

[0075] Notable non-limiting examples of coupling agents include, for example, "symmetric" or "asymmetric" silane polysulfides, more specifically, bis((C1-C4)alkoxyl(C1-C4)alkylsilyl(C1-C4)alkyl) polysulfides (specifically disulfides, trisulfides, or tetrasulfides), such as bis(3-(trimethoxysilyl)propyl) polysulfide or bis(3-(triethoxysilyl)propyl) polysulfide, such as triethoxysilylpropyl tetrasulfide. Also included are monoethoxydimethylsilylpropyl tetrasulfide. Also included are silanes containing masked or free thiol or thioester functional groups, such as 3-octanoylthio-1-propyltriethoxysilane.

[0076] The coupling agent may optionally be combined with a suitable "coupling activator", ie a compound that is mixed with the coupling agent to increase the effectiveness of the latter.

[0077] The weight proportion of the silica of the invention in the polymer composition can vary within a fairly wide range. The weight proportion usually represents from 10% to 200%, in particular from 20% to 150%, of the weight of the polymer. In one embodiment, the precipitated silica of the invention may represent from 20% to 80%, for example from 30% to 70%, of the weight of the polymer. In an alternative embodiment, it may represent from 80% to 120%, for example from 90% to 110%, of the weight of the polymer.

[0078] A particular object of the present invention is a composition comprising the precipitated silica of the invention, typically in an amount between 20% and 150% by weight of the polymer, and at least one polymer selected from the group consisting of diene elastomers, natural rubber and epoxidized natural rubber as detailed above.

[0079] The silica of the invention may advantageously constitute all of the reinforcing inorganic filler and even all of the reinforcing filler of the polymer composition.

[0080] The composition comprising the precipitated silica of the present invention can be used for the manufacture of many articles.Non-limiting examples of finished products comprising the precipitated silica of the present invention and the above-mentioned composition are, for example, shoe soles, flooring, gas barriers, flame retardant materials, and also engineering parts, such as rollers for cableways, seals for household appliances, seals for liquid or gas pipes, brake system seals, pipes (flexible), sheathing (especially cable sheathing), cables, engine supports, battery separators, conveyor belts or transmission belts.The composition of the present invention can be advantageously used in the manufacture of tires and tire parts.

[0081] A further object of the invention is a tire or tire component comprising the precipitated silica of the invention.

[0082] To the extent that the disclosure of any patents, patent applications, and publications incorporated herein by reference conflicts with the statements of this application to the extent that a term may be unclear, this statement shall control.

[0083] The present invention will now be described with reference to the following examples, the purposes of which are merely illustrative and are not intended to limit the scope of the invention. EXAMPLES

[0084] Analysis method The physicochemical properties of the precipitated silica of the invention were determined using the methods described below.

[0085] CTAB surface area The CTAB surface area was determined according to standard NF ISO5794-1, Appendix G (June 2010).

[0086] Determination of total carbon content The total carbon content was measured using a carbon / sulfur analyzer such as the Horiba EMIA 320 V2. The principle of the carbon / sulfur analyzer is based on the combustion of a solid sample in a flow of oxygen in an induction furnace (adjusted to about 170 mA) in the presence of a combustion promoter (about 2 g of tungsten (specifically Lecocel 763-266), about 1 g of iron, and about 0.25 g of tin). The carbon present in the sample to be analyzed (weighing about 0.2 grams) combines with oxygen to form CO2, CO. These gases are then analyzed by an infrared detector. Moisture from the sample and water produced during these oxidation reactions is removed by passing it over a cartridge containing a dehydrating agent (magnesium perchlorate) so as not to interfere with the infrared measurement.

[0087] The results are expressed as the weight percent of elemental carbon relative to the weight of the silica sample.

[0088] 13 C NMR spectroscopy The products were analyzed by 1D spectroscopy on a Bruker Avance Solid State 300 spectrometer operating at 7.04 T. 13 Characterization was performed by MAS NMR spectroscopy. A commercial 4 mm high-speed probe (DVT4) with a spinning frequency of 10 KHz was used with cross polarization at 90° pulses, 3 ms contact time, and 5 s recycle time, and 10000-20000 transients. The region of the spectrum analyzed for identification of methyl resonances was from -15 to 10 ppm.

[0089] Calibration was performed against adamantane, which is characterized by two chemical shifts at 38.5 ppm and 29.4 ppm.

[0090] Working Example Example 1 Into a 25 L stainless steel reactor were introduced 8.6 L purified water, 169 g NaSO (solid), 5.38 kg sodium silicate solution (SiO / NaO ratio=3.42, SiO concentration=18.9 wt.-%, used in all steps of the process) and 132 g potassium methyl silicate solution (SILRES® BS 16, Wacker Chemie AG, SiO concentration: 8.12 wt.-%).

[0091] The resulting solution was stirred and heated to 79°C. A 7.7 wt% sulfuric acid solution was then introduced into the reactor at a flow rate of 109 g / min over a period of 20 minutes. After this initial step, a 7.7 wt% sulfuric acid solution was added at a flow rate of 177 g / min until the reaction medium reached a pH value of 8.0. During the first 20 minutes of sulfuric acid addition, the temperature of the reaction medium was 79°C. The reaction medium was then heated to 92°C for about 7 minutes. The remainder of the precipitation reaction was carried out at this temperature.

[0092] At the same time, sodium silicate and a 7.7% by weight solution of sulfuric acid were introduced at a flow rate of 64.4 g / min over a period of 20 minutes, the flow rate of the 7.7% by weight solution of sulfuric acid being adjusted so as to maintain the pH of the reaction medium at a value of 8.0.

[0093] At the end of the simultaneous addition, the pH of the reaction medium was brought to a value of 4.8 using 7.7% by weight sulfuric acid at a flow rate of 120 g / min. The reaction mixture was left for 5 minutes. A suspension of precipitated silica was obtained.

[0094] The suspension was filtered and washed with a filter press. The filter cake thus obtained was mechanically decomposed by adding a sodium aluminate solution (Al2O3 concentration: 12 wt%) to obtain an Al / SiO2 concentration of 3000 ppm. The pH of the obtained silica suspension was brought to 6.2 by adding a 7.7 wt% sulfuric acid solution.

[0095] The obtained suspension was dried by a nozzle spray dryer to obtain precipitated silica S1, the characteristics of which are reported in Table 1.

[0096] Example 2 Into a 25 L stainless steel reactor were introduced 12.6 L purified water, 129.5 g Na2SO4 (solid), 4.07 kg sodium silicate solution (SiO2 / Na2O ratio=3.42, SiO2 concentration=18.9 wt.%, used throughout the process), 149 g potassium methylsilicate solution (SILRES® BS16, Wacker Chemie AG, SiO2 concentration: 8.12 wt.%).

[0097] The resulting solution was stirred and heated to reach 95° C., at which temperature all reactions were carried out.

[0098] A 95% by weight solution of sulfuric acid was introduced into the reactor at a flow rate of 6.9 g / min over a period of 25 minutes. After this first step, a 95% by weight solution of sulfuric acid was added at a flow rate of 219 g / min until the pH value of the reaction medium reached 8.0.

[0099] At the same time, sodium silicate, with a flow rate of 64.9 g / min, and a 96% by weight sulfuric acid solution were introduced over a period of 10 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.0.

[0100] At the end of this simultaneous addition, the pH of the reaction medium was brought to a value of 4.7 using 96% by weight sulfuric acid at a flow rate of 123 g / min. The reaction mixture was left for 5 minutes. A suspension of precipitated silica was obtained.

[0101] The suspension was filtered and washed with a filter press. The filter cake thus obtained was mechanically decomposed by adding a sodium aluminate solution (Al2O3 concentration: 12 wt%) to obtain an Al / SiO2 concentration of 3000 ppm. The pH of the obtained silica suspension was brought to 6.2 by adding a 7.7 wt% sulfuric acid solution.

[0102] The obtained suspension was dried by a nozzle type spray dryer to obtain precipitated silica S2. The properties of precipitated silica S2 are reported in Table 1.

[0103] Example 3 In a 25 L stainless steel reactor, 13.4 L of purified water and 209 g of Na2SO4 (solid) were introduced. The resulting solution was stirred and heated to reach 92°C. All reactions were carried out at this temperature. A 7.7% by weight solution of sulfuric acid was metered into the reactor until the pH of the medium reached a value of 3.8.

[0104] 165 g of potassium methyl silicate solution (SILRES® BS 16, Wacker Chemie AG, SiO2 concentration: 8.12% by weight) were metered into the reaction medium over a period of 1 minute.

[0105] A sodium silicate solution (SiO2 / Na2O ratio=3.4, SiO2 concentration=19.4% by weight) and a 7.7% by weight sulfuric acid solution were simultaneously introduced into the reactor over a period of 25 minutes at a flow rate of 92.2 g / min. The flow rate of the sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.2.

[0106] The introduction of acid was stopped, while maintaining the silicate addition at the same flow rate, until the reaction medium reached a value of 8.0.

[0107] Simultaneously, over a period of 18 minutes, sodium silicate and a 7.7% by weight solution of sulfuric acid were metered in at a flow rate of 150 g / min. The flow rate of the sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.0.

[0108] At the end of the simultaneous addition, the pH of the reaction medium was brought to 4.8 with 7.7% by weight of sulfuric acid. The reaction mixture was left for 5 minutes.

[0109] The silica suspension thus obtained was filtered and washed with a filter press. The filter cake thus obtained was mechanically decomposed by adding a sodium aluminate solution (Al2O3 concentration: 12% by weight) to obtain an Al / SiO2 concentration of 3000 ppm. The pH of the silica suspension obtained was brought to 6.2 by adding a 7.7% by weight sulfuric acid solution. The characteristics of the precipitated silica S3 are reported in Table I.

[0110] Example 4 Into a 25 L stainless steel reactor were introduced 6.98 L purified water, 149.5 g NaSO (solid), 5.59 kg sodium silicate solution (SiO / NaO ratio = 3.43, SiO concentration = 19.4 wt.-%, used in all steps of the process) and 471 g potassium methyl silicate solution (SILRES® BS 16, Wacker Chemie AG, SiO concentration: 10 wt.-%).

[0111] The resulting solution was stirred and heated to reach 80° C. Then, a 7.7% by weight sulfuric acid solution was introduced into the reactor at a flow rate of 110 g / min over a period of 20 minutes. After this first step, a 7.7% by weight sulfuric acid solution was added at a flow rate of 110 g / min until the reaction medium reached a pH value of 8.0. During the first 20 minutes of the addition of the sulfuric acid solution, the temperature of the reaction medium was 80° C. Then, the reaction medium was heated to 92° C. in about 7 minutes. The remainder of the precipitation reaction was carried out at this temperature.

[0112] At the same time, sodium silicate and a 7.7% by weight solution of sulfuric acid were introduced at a flow rate of 58 g / min over a period of 20 minutes. The flow rate of the 7.7% by weight solution of sulfuric acid was adjusted so as to maintain the pH of the reaction medium at a value of 8.0.

[0113] At the end of the simultaneous addition, the pH of the reaction medium was brought to a value of 5.5 using a 7.7% by weight sulfuric acid solution at a flow rate of 73 g / min. The reaction mixture was left to stand for 5 minutes. A suspension of precipitated silica was obtained. The suspension was filtered and washed with a filter plate. The filter cake obtained was mechanically disintegrated and water was added to obtain a SiO2 suspension with 15% silica S4.

[0114] The packing density of Silica S4 is 0.32 g / cm 3 The properties of Silica S4 are shown in Table 1.

[0115] TIFF0007602568000001.tif57161

[0116] Comparative silica CS1: A sample of Zeosil® 1165MP (available from Solvay SA) provided in powder form.

[0117] Comparative Silica CS2: A sample of Zeosil® Premium 200MP (available from Solvay SA) provided in powder form.

[0118] General Procedure for Preparation of Rubber Compositions The rubber compositions were prepared using a process comprising two successive preparation stages: a first stage of high temperature thermomechanical processing, followed by a second stage of mechanical processing at a temperature below 110°C to introduce the vulcanization system.

[0119] The first stage was carried out using a Brabender brand internal mixer type mixer (Example 4: 70 mL volume, Example 5: 380 mL volume). The initial temperature and rotor speed were set so that the mixture drop temperature was about 140-160°C.

[0120] In the first pass of the first stage, the elastomer and silica (introduced separately) were mixed with the coupling agent and stearic acid, the duration being 4-10 minutes.

[0121] After cooling the mixture (temperature below 100° C.), zinc oxide and stabilizers / antioxidants were introduced during a second pass, the duration of which ranged from 2 to 5 minutes.

[0122] After cooling the mixture (temperature below 100° C.), the vulcanization system (sulfur and accelerator, e.g., CBS) was added to the mixture during the second stage, which was carried out in an open mill preheated to 50° C. The duration of this stage was 2 to 6 minutes.

[0123] Each final mixture was then calendered into the form of 2-3 mm thick plaques for evaluation of mechanical and dynamic properties.

[0124] Determination of mechanical and dynamic properties of vulcanizates Measurements were carried out on optimally vulcanized compositions (T98) at the following temperatures: Example 4: 150°C, Example 5: 160°C.

[0125] Shore A hardness measurements of the vulcanizates were performed according to standard ASTM D 2240. The values ​​given were measured in 3 seconds.

[0126] Uniaxial tensile tests were performed on an Instron 5564 machine at a speed of 500 mm / min on specimens of type H2 according to standard NF ISO 37. A modulus of 300% corresponds to the stress measured at a tensile strain of 300%.

[0127] Tear strength tests were carried out according to standard NF ISO 34 using specimen B on an Instron 5564 machine at a speed of 500 mm / min.

[0128] Loss factor (tan δ) and dynamic tensile modulus (E') values ​​were measured for vulcanized specimens (cylindrical specimens, section 95 mm 2 The deformation was recorded for a range of 10 mm (height and width 14 mm). The samples were subjected to a pre-strain with a sinusoidal deformation of 10% and a dynamic solicitation of 4%. The measurements were carried out on a Metravib VA 3000 instrument at 60° C. and a frequency of 10 Hz.

[0129] Example 5 The rubber compositions described in Table 2 were prepared according to the general procedure described above. The amounts of each component are expressed as parts by weight per 100 parts of the total amount of elastomer (phr). The results of the mechanical and dynamic tests are also reported in Table 2.

[0130] TIFF0007602568000002.tif178161

[0131] Compared to precipitated silica (CS1) not modified with alkyl moieties, the silica according to the invention (S1) provides polymer compositions with higher stiffness (E'60°C), better elongation at break and higher tensile strength.

[0132] Example 6 The rubber compositions described in Table 3 were prepared according to the general procedure described above. The amounts of each component are expressed as parts by weight per 100 parts of the total amount of elastomer (phr). The results of the mechanical and dynamic tests are also reported in Table 3.

[0133] TIFF0007602568000003.tif217161

[0134] Compared to precipitated silicas not modified with alkyl moieties (CS2), the silica according to the invention (S2) exhibits high stiffness, good tensile strength, elongation at break and tear strength without an increase in energy dissipation at 60°C (tan δ(60°C)).

Claims

1. A precipitated silica comprising alkyl moieties chemically bonded to at least a portion of the Si atoms in the silica structure, the alkyl moieties being assigned to methyl groups of the alkyl moieties. 13 A precipitated silica characterized by a C NMR spectrum resonance between -2.5 and -4.5 ppm.

2. 2. The precipitated silica of claim 1, wherein said chemically bonded alkyl moieties are selected from the group consisting of methyl, ethyl and propyl groups.

3. 3. The precipitated silica of claim 2, wherein said chemically bonded alkyl moieties are methyl groups.

4. 4. Precipitated silica according to claim 1, having a carbon content of between 0.2% and 15.0% by weight, relative to the silica.

5. 40 to 600 m 2 4. Precipitated silica according to claim 1, characterized by a CTAB surface area in the range of 0.1 to 0.5 nm / g.

6. A process for preparing precipitated silica according to any one of claims 1 to 5, comprising reacting a silicate with an acid in a reaction medium by a precipitation reaction to produce a suspension of precipitated silica, said precipitation reaction including at least one step in which a total amount of at least one alkali metal alkyl siliconate is provided to the reaction medium before 50% of the precipitation reaction has taken place.

7. A composition comprising a precipitated silica according to any one of claims 1 to 5 and at least one elastomer.

8. An article comprising a precipitated silica according to any one of claims 1 to 5 or a composition according to claim 7.

9. 10. The article of claim 8 in the form of a tire.

Citation Information

Patent Citations

  • Graphic Design (Two Dimensional)

    GB6007427S

  • Molecular and oligomeric silanes that are precursors of network materials

    JP1999508561A

  • Precursor of compound containing flexible organic portion and rigid inorganic portion

    JP2007051152A

  • Use of pretreated precipitated silica as reinforcing filler for silicone elastomers and curable silicone elastomer compositions obtained by cold mixing

    JP2007519793A

  • Novel method for preparing precipitated silica, novel precipitated silica and its use, especially for reinforcing polymers

    JP2017511788A